ANALISIS NILAI-NILAI PENDIDIKAN ISLAM DALAM KITAB WASHOYA ABAA’LIL ABNAA’ KARANGAN SYEKH SYAKIR AL ISKANDARY - Dewi Kumalasari; Rofiqotul Aini (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2023)
The importance of Islamic educational values lies in efforts to produce Muslim individuals who are responsible, ethical and able to make positive contributions to society. The book Washoya al-aba'lil abna' is a book that has been taught in many Islamic boarding schools for decades. This book was created because many students began to show signs of moral decline, in order to protect them from the rampant attempts to destroy morals. This research was conducted based on a literature review or Literature Survey. Natural research is library research. collect and analyze pure data from documentary literature such as journal articles or books and are still under research. The values of moral education in the book Washoya Al-Aba'' Lil Abna'' not only focus on tendencies in learning and teaching but also describe how a child should be devoted to Allah and His Messenger as well as good morals in everyday life to yourself and others.